PEMAHAMAN GURU BIOLOGI TERHADAP KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DI SMA NEGERI KABUPATEN KUANSING TAHUN 2013 - Darmawati '; Wan Syafi’i; R. Asri Febri Siska (Program Studi Pendidikan Biologi, 2013)
The research has been to know understanding of the biology teachers to the unit level education curriculum (KTSP) at SMAN in Kuansing regency 2013 year. This typenof research is a descriptive study. The sample was biology teachers SMAN in Kuansing regencies, with indicators the concept of unit level education curriculum (KTSP), development program, implementation of learning, and evaluation of learning. Data collection technique using written tests total of 30 question. From the research results obtained percentage understanding teachers can be seen from the indicators concept KTSP is 60,2% (quite category). The development program is 67,7% (quite category). The implementation of learning is 75,6% (good category). And the evaluation of learning is 65,8% (quite category). From the research results can be concluded that understanding of the biology teachers to the unit level education curriculum (KTSP) at SMAN in Kuansing regencies 2013 year is 67,3% (quite category).Keywords: Understanding, Biology teachers, KTSP